Depressive Symptoms, Pain, Chronic Medical Morbidity, and Interleukin‐6 among Primary Care Patients. Issue 5 (22nd April 2013) - Poleshuck, Ellen L.; Talbot, Nancy L.; Moynihan, Jan A.; Chapman, Benjamin P.; Heffner, Kathi L.
Abstract Objective Pain, chronic medical morbidity, and depression are highly prevalent problems that frequently co‐occur in primary care. Elevated levels of inflammatory markers are linked with all three of these conditions and may play an important role in patients' comorbidities. The current study aimed to examine if the associations among pain, chronic medical morbidity, and the inflammatory marker interleukin (IL)‐6 are dependent on depression status in primary care patients. Setting, Subjects, and Outcome Measures Primary care patients (N = 106) aged 40 and older were assessed for pain (36‐item Medical Outcomes Study Survey Form), chronic medical morbidity (checklist of chronic health conditions), and depressive symptoms (Center for Epidemiologic Studies Depression Scale), and provided a blood sample for the measurement of serum IL‐6. Results Among patients with elevated depressive symptoms, higher IL‐6 levels were associated with both greater pain and greater chronic medical comorbidity. IL‐6 was unrelated to pain or chronic medical comorbidity among patients without clinically significant depressive symptoms. In mediation analyses, chronic medical morbidity did not mediate the association between IL‐6 and pain, and depression severity and pain remained independently associated after adjustment for chronic medical comorbidity. Conclusions Depression may increase primary care patients' vulnerability to pain and elevated levels of inflammatory markers such as IL‐6.